2x2-2x=(x-1)2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
x4-x3+x2-x=0
x2(x2-x)+x(x2-x)=0
(x2-x)(x2+x)=0
\(\Rightarrow\hept{\begin{cases}x^2-x=0\\x^2+x=0\end{cases}}\Leftrightarrow x=0\)
\(\left(x+7\right)^2-5x-35=0\)
\(\Rightarrow\left(x+7\right)^2-5.\left(x+7\right)=0\)
\(\Rightarrow\left(x+7\right).\left(x+7-5\right)=0\)
\(\Rightarrow\left(x+7\right).\left(x+2\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x+7=0\\x+2=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=-7\\x=-2\end{cases}}\)
y(x - 2) + 3x + 6
= xy - 2y + 3x + 6
= 2010.(-1) - 2.(-1) + 3.2010 + 6
= 4028
\(2x^2-2x=\left(x-1\right)^2\Leftrightarrow2x^2-2x=x^2-2x+1\)
\(\Leftrightarrow x^2=1\Leftrightarrow x=\pm1\)